The Madre de Aguas of Cuba - Gidwitz, Adam; Otheguy, Emma; Casey, Jesse; Smith, Chris Lenox (Gidwitz, Adam. Unicorn Rescue Society, 2020)
"A legendary sea serpent is missing. Can the Unicorn Rescue Society find it ... and end Cuba's terrible drought?" "--Page 4 of cover